Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M186 - Schmidt, Christopher; Klein, Johanna; Schumacher, Mia (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV METEOR during cruise M186 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 2022-11-29 (Lisbon) – 2022-12-31 (Las Palmas) in the Northern Atlantic Ocean. The main objective of M186 was to explore fluid dynamics of sediment hosted hydrothermal fluid seeps on the Azores Plateau. Data were recorded within the Azores EEZ. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project and published according to the FAIR principles..
Keywords: Bathymetry; DAM; EM122; Multibeam; raw data